**Symmetric Function :**

An **algebraic expression** in a and b, which remains unchanged, when a and b are interchanged is known as **symmetric function** in a and b.

For example, *α*^{2} + *β*^{2} and *α*^{3} + *β*^{3} etc. are symmetric functions.

Symmetric function is to be expressed in terms of (*α* + *β*) and *α**β*. So, this can be evaluated for a given quadratic equation.

Some useful relations involving *α* and *β*

1. *α*^{2} + *β*^{2} = (*α* + *β*)^{2} – 2*α**β*

2. (*α* – *β*)^{2} = (*α* + *β*)^{2} – 4*α**β*

3. *α*^{2} – *β*^{2} = (*α* + *β*) (*α* – *β*) = (*α* + *β*)

4. *α*^{3} + *β*^{3} = (*α* + *β*)^{3} – 3*α**β* (*α* + *β*)

5. *α*^{3} – *β*^{3} = (*α* – *β*)^{3} + 3*α**β* (*α* – *β*)

6. *α*^{4} + *β*^{4}= [(*α* + *β*)^{2} – 2*α**β*]^{2} –2(*α**β*)^{2}

7. *α*^{4} – *β*^{4} = (*α*^{2} + *β*^{2}) (*α*^{2} – *β*^{2}) then use (1) and (3)

Example: If a and b are the zeroes of the polynomial ax^{2}+ bx + c. Find the value of (i)α–β(ii)α^{2}–β^{2}.

Solution: Since a and b are the zeroes or roots of the polynomial ax^{2} + bx + c.

⇒ a + b = – ; ab =

(i) (a – b)^{2} = (a + b)^{2} – 4ab

= = –=

a – b =

(ii) a^{2} + b^{2} = a^{2} + b^{2} + 2ab – 2ab

= (a + b)^{2} – 2ab

= – 2 =

Example: If a and b are the zeroes or roots of the quadratic polynomial ax^{2}+ bx + c. Find the value of (i) a^{2}– b^{2}(ii) a^{3}+ b^{3}.

Solution: Since a and b are the zeroes of ax^{2} + bx + c

⇒ a + b = –, ab =

(i) a^{2} – b^{2} = (a + b) (a – b)

= –

= –= –

= –

(ii) a^{3} + b^{3} = (a + b) (a^{2} + b^{2} – ab)

= (a + b) [(a^{2} + b^{2} + 2ab) – 3ab]

= (a + b) [(a + b)^{2} – 3ab]

= –

=–

=

=

If you want to give information about online courses to other students, then share it with more and more on Facebook, Twitter, Google Plus. The more the shares will be, the more students will benefit. The share buttons are given below for your convenience.

SHOW CHAPTERS